Análise das colmeias de mídias sociais nas instituições de ensino superior - de Almeida, Rafael; Maciel, Cristiano; Souza, Patrícia Cristiane (Anais do Workshop sobre Aspectos da Interação Humano-Computador na Web Social (WAIHCWS), 2017)
Currently, public and private institutions seeking to keep close to technological advances in terms of information and communication technologies. This perspective that the institutions are faced with the "Social Web", an era where the relationship and communication over the Internet is one of the main goals. Assuming the mission of creating a bridge between the technological relations Social Media have subsidized much access of institutions to this web social universe. This paper’s objective is to present an overview of how Higher Education Institutions (HEI) has officially adopted the use of social media are behaving regarding aspects defended by Gene Smith in their hive of social media.